2022
DOI: 10.1016/j.cub.2021.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fishery facilitates a novel transmission pathway in an emerging animal reservoir of Guinea worm

Abstract: Highlights d Reservoirs of infection in dogs impede eradication of human Guinea worm disease d We analyzed disease risk in dogs in Chad where Guinea worm is most common d Disease is associated with consumption of fish made available by seasonal fisheries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“… 16 They have also shown that viable D. insignis larvae can survive in tadpoles/frogs for 4 to 8 months in the laboratory. 14 Other studies have associated increased risk of Guinea worm infections in Chadian dogs with consumption of fish, 17 and consumption of raw fish guts (Eugene Liu, unpublished data). A small study by The Carter Center and Chadian staff of households with and without infected dogs suggests that dogs that accompanied their owners to mass fishing or were allowed to wander their village alone—both of which provide access to discarded fish or fish guts—are at greater risk of Guinea worm infection (Sarah Yerian, unpublished data).…”
Section: Current Status Of the Campaignmentioning
confidence: 99%
“… 16 They have also shown that viable D. insignis larvae can survive in tadpoles/frogs for 4 to 8 months in the laboratory. 14 Other studies have associated increased risk of Guinea worm infections in Chadian dogs with consumption of fish, 17 and consumption of raw fish guts (Eugene Liu, unpublished data). A small study by The Carter Center and Chadian staff of households with and without infected dogs suggests that dogs that accompanied their owners to mass fishing or were allowed to wander their village alone—both of which provide access to discarded fish or fish guts—are at greater risk of Guinea worm infection (Sarah Yerian, unpublished data).…”
Section: Current Status Of the Campaignmentioning
confidence: 99%
“…For, instance, it has been recently demonstrated that the emergence of animal reservoirs of Dracunculus medinensis , particularly in fish-consuming domestic dogs (93% of all Guinea worms detected worldwide in 2020 were in dogs in Chad), has become the major impediment to eradication of this human disease. 3 4 For human African trypanosomiasis, the importance of latent infections in seropositive asymptomatic individuals, 5 the identification of domestic pigs as reservoirs of Trypanosoma brucei gambiense 6 and the probable role of skin-dwelling trypanosomes in transmission maintenance 7 8 are active research areas that may be crucial for reaching the elimination goal. 9 Actually, the lack of fundamental scientific knowledge about the natural reservoirs and even the transmission of Mycobacterium ulcerans, that still remain elusive in most endemic areas, 10 is also pointing to the crucial need for more fundamental knowledge on NTDs.…”
Section: Impact Of Multidisciplinary Fundamental Research On Ntd Controlmentioning
confidence: 99%
“…Some of these challenges originate from the discovery of new key fundamental aspects of pathogens’ maintenance and/or transmission. For, instance, it has been recently demonstrated that the emergence of animal reservoirs of Dracunculus medinensis , particularly in fish-consuming domestic dogs (93% of all Guinea worms detected worldwide in 2020 were in dogs in Chad), has become the major impediment to eradication of this human disease 3 4. For human African trypanosomiasis, the importance of latent infections in seropositive asymptomatic individuals,5 the identification of domestic pigs as reservoirs of Trypanosoma brucei gambiense 6 and the probable role of skin-dwelling trypanosomes in transmission maintenance7 8 are active research areas that may be crucial for reaching the elimination goal 9.…”
Section: Impact Of Multidisciplinary Fundamental Research On Ntd Controlmentioning
confidence: 99%
“…The animal reservoirs of Dracunculiasis medinensis (particularly in dogs) has become one of the major obstacles to global eradication of this human parasitosis. A novel pathway for transmission of Guinea worm in dogs, involving consumption of fish, have been hypothesized to support the maintenance of this animal reservoir (Goodwin et al, 2021). The incidence rates are influenced by rainfall: in arid areas the infestation peak is in the rainy season, while in wet areas, the number of infestations increases when water supplies are limited (Greenaway, 2004).…”
Section: Dracunculiasismentioning
confidence: 99%